2017
DOI: 10.1186/s13071-017-2329-8
|View full text |Cite
|
Sign up to set email alerts
|

A synoptic overview of golden jackal parasites reveals high diversity of species

Abstract: The golden jackal (Canis aureus) is a species under significant and fast geographic expansion. Various parasites are known from golden jackals across their geographic range, and certain groups can be spread during their expansion, increasing the risk of cross-infection with other carnivores or even humans. The current list of the golden jackal parasites includes 194 species and was compiled on the basis of an extensive literature search published from historical times until April 2017, and is shown herein in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 157 publications
0
59
0
4
Order By: Relevance
“…Regarding golden jackal (Canis aureus) moderate prevalence rates of Toxascaris leonina have been reported around the world, such as in Azerbaijan (31.8%), Bulgaria (36%) and Russia (43.5%). The prevalence of T. canis in this wildlife species ranges 40-61% in Asia and 20-54.5% in European countries, whereas T. cati was only detected in jackals dwelling in Russia (5-26%) [49,62]. Considering that there are only 4 golden jackal studies and 2 red fox (Vulpes vulpes) studies, there exist paucity of data on Toxocara/Toxascaris prevalence in wild canine and feline fauna of Iran, which highlights more subtle investigations.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding golden jackal (Canis aureus) moderate prevalence rates of Toxascaris leonina have been reported around the world, such as in Azerbaijan (31.8%), Bulgaria (36%) and Russia (43.5%). The prevalence of T. canis in this wildlife species ranges 40-61% in Asia and 20-54.5% in European countries, whereas T. cati was only detected in jackals dwelling in Russia (5-26%) [49,62]. Considering that there are only 4 golden jackal studies and 2 red fox (Vulpes vulpes) studies, there exist paucity of data on Toxocara/Toxascaris prevalence in wild canine and feline fauna of Iran, which highlights more subtle investigations.…”
Section: Discussionmentioning
confidence: 98%
“…Among the flea species of wild carnivores, P. irritans was collected here from the golden jackal. Based on a recent review [ 20 ], the golden jackal was not reported to be a host of P. irritans in central Europe. Thus, the present findings contribute to the increasingly recognized epidemiological significance of this wild carnivore, which has an expanding geographical range in Europe [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In jackals, both E. multilocularis (13.1%) and E. granulosus (3.3%) were found. Infection of this canid with these species of Echinococcus has been reported on multiple occasions and across a wide geographical range [52]. In Iran, infections in jackals with E. multilocularis has been reported from Ardabil Province in the northwest [32] and Razavi Khorasan Province in the northeast of Iran [33].…”
Section: Discussionmentioning
confidence: 99%
“…In Hungary, the jackal was recently reported as a new host record for E. multilocularis [53]. The jackal is under significant and fast geographical expansion [52] and can migrate long distances through ecological corridors [53]. Since this species is an important definitive host for echinococcosis, it can serve as a potential source of infection to humans and domestic animals in endemic areas.…”
Section: Discussionmentioning
confidence: 99%